Trends in teacher training at the University of Colima (Papeles, 2026)
Introduction: This study analyzes trends in teacher training at the University of Colima during the period 2020-2024. The research question is: What trends characterize university teacher training at the University of Colima, based on an analysis of institutional training activities developed between July 2020 and July 2024? This analysis is relevant in the context of post-pandemic educational transformation. Methodology: A descriptive, longitudinal design was adopted, based on a review of the training programs published on the institutional website. The analysis employed a summative content approach, using a system of categories constructed from theoretical and empirical criteria. The unit of analysis was each scheduled training event. Data were processed using frequencies, percentages, and cross-tabulations, allowing for the examination of their distribution and evolution over time. Results and Discussion: 437 training activities were identified, corresponding to nine sessions during the analyzed period. Academic events predominated in the following areas: didactics, socio-emotional development, and research. Educational modalities included both in-person and online learning, and workshop and course-workshop formats were the most common. The study also highlighted the concentration of activities in the continuing professional development stage for teachers (90,61 %), in contrast to the initial and specialization stages. A total of 520 facilitators participated, 89,23 % of whom were faculty members of the institution. Conclusions: The findings demonstrate a reconfiguration of teacher training toward more flexible, diversified, and relevant models. The need to consolidate institutional strategies that integrate multidisciplinarity, pedagogical innovation, and attention to the emerging needs of the teaching profession is emphasized.
Keywords: Training course; higher education; teacher training; training methods; post-covid-19 pandemic; educational trend